Immunolocalization of the Four Prostaglandin E2 Receptor Proteins EP1, EP2, EP3, and EP4 in Human Kidney - RUTA MORATH; Thomas Klein; Hannsjörg W. Seyberth; Rolf M. Nüsing (1999)
Abstract. Four prostaglandin E 2 receptor subtypes designated EP1, EP2, EP3, and EP4 have been shown to mediate a variety of effects of prostaglandin E 2 (PGE 2 ) on glomerular hemodynamics, tubular salt and water reabsorption, and on blood vessels in the human kidney. Despite the important role of renal PGE 2 , the localization of PGE 2 receptor proteins in the human kidney is unknown. The present study used antipeptide antibodies to the EP1 to EP4 receptor proteins for immunolocalization in human kidney tissue. Immunoblot studies using these antibodies demonstrated distinct bands in membrane fraction from human kidney. By means of immunohistochemistry, expression of the human EP1 receptor subtype protein in renal tissue was detected mainly in connecting segments, cortical and medullary collecting ducts, and in the media of arteries and afferent and efferent arterioles. The human EP2 receptor subtype protein was detectable only in the media of arteries and arterioles. The human EP3 receptor subtype protein was strongly expressed in glomeruli, Tamm-Horsfall negative late distal convoluted tubules, connecting segments, cortical and medullary collecting ducts, as well as in the media and the endothelial cells of arteries and arterioles. Staining of the human EP4 receptor subtype protein was observed in glomeruli and in the media of arteries. However, no signal of either receptor subtype was detected in the thick ascending limb, the macula densa, or in adjacent juxtaglomerular cells. These results support the concept that PGE 2 modulates specific functions in different anatomical structures of the human kidney.